2018
DOI: 10.4028/www.scientific.net/msf.915.185
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Metal-Ceramic Interfaces: Wetting of Alumina by Molten Aluminum

Abstract: Interfacial behavior of Al and α-Al2O3 are investigated via molecular dynamic simulation (MD) employing reactive force fields parameterized for Al and Al2O3. The main result of this work is elucidating the wetting behavior and interface chemistry of molten aluminum on the α-Alumina (0001) surface through MD simulations. Wetting and interface chemistry are studied at 8 different temperatures from 700 to 1400 K for four different droplet sizes: with 16, 24, 32 and 40 Å diameters. Chemical reactions are observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The present results are consistent with previous computational and experimental studies of the wetting process. For example, recently, Tigli et al employed ReaxFF reactive MD simulations to investigate the wetting processes in an Al and alumina system [34]. They revealed that some of the oxygen atoms diffused into the molten Al droplet within a range of 10 Å, which indicated that the solubility limit of oxygen in liquid Al droplets was very limited.…”
Section: Results On a Spherical Nanodropletmentioning
confidence: 99%
“…The present results are consistent with previous computational and experimental studies of the wetting process. For example, recently, Tigli et al employed ReaxFF reactive MD simulations to investigate the wetting processes in an Al and alumina system [34]. They revealed that some of the oxygen atoms diffused into the molten Al droplet within a range of 10 Å, which indicated that the solubility limit of oxygen in liquid Al droplets was very limited.…”
Section: Results On a Spherical Nanodropletmentioning
confidence: 99%